A method to confer Protein L binding ability to any antibody fragment. Issue 2 (17th February 2016) - Lakhrif, Zineb; Pugnière, Martine; Henriquet, Corinne; di Tommaso, Anne; Dimier-Poisson, Isabelle; Billiald, Philippe; Juste, Matthieu O.; Aubrey, Nicolas
Abstract: Recombinant antibody single-chain variable fragments (scFv) are difficult to purify homogeneously from a protein complex mixture. The most effective, specific and fastest method of purification is an affinity chromatography on Protein L (PpL) matrix. This protein is a multi-domain bacterial surface protein that is able to interact with conformational patterns on kappa light chains. It mainly recognizes amino acid residues located at the VL FR1 and some residues in the variable and constant (CL ) domain. Not all kappa chains are recognized, however, and the lack of CL can reduce the interaction. From a scFv composed of IGKV10-94 according to IMGT®, it is possible, with several mutations, to transfer the motif from the IGKV12-46 naturally recognized by the PpL, and, with the single mutation T8P, to confer PpL recognition with a higher affinity. A second mutation S24R greatly improves the affinity, in particular by modifying the dissociation rate (kd ). The equilibrium dissociation constant (KD ) was measured at 7.2 10 -11 M by surface plasmon resonance. It was possible to confer PpL recognition to all kappa chains. This protein interaction can be modulated according to the characteristics of scFv (e.g., stability) and their use with conjugated PpL. This work could be extrapolated to recombinant monoclonal antibodies, and offers an alternative for protein A purification and detection.